2017
DOI: 10.1080/23802359.2017.1280696
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of a cavefishSinocyclocheilus ronganensis(Cypriniformes: Cyprinidae)

Abstract: In this study, we report the complete mitochondrial genome of Sinocyclocheilus ronganensis. The whole mitochondrial genome is 16,587 bp with an accession number KX778473, and consists of 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs genes, and a 936 bp control region. Phylogenetic analysis shows that S. ronganensis is close to cave-restricted S. anophthalmus and surface-dwelling S. grahami. The complete mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…To validate the phylogenetic position of S. yishanensis, a neighbour-joining (NJ) tree inferred from the whole mitogenome of 14 Sinocyclocheilus species and two outgroup species (Cyprinus cario and Danio rerio) was constructed with 1000 bootstrap replicates using MEGA 6.06. The phylogenetic results revealed that all Sinocyclocheilus species clustered as one monophyletic clade except S. jii, and S. yishanensis was the most close to S. ronganensis (Luo et al 2017), it was consistent with the BLAST results (92% identities to the mitogenome of S. ronganensis) and morphological comparison results (Figure 1).…”
supporting
confidence: 85%
“…To validate the phylogenetic position of S. yishanensis, a neighbour-joining (NJ) tree inferred from the whole mitogenome of 14 Sinocyclocheilus species and two outgroup species (Cyprinus cario and Danio rerio) was constructed with 1000 bootstrap replicates using MEGA 6.06. The phylogenetic results revealed that all Sinocyclocheilus species clustered as one monophyletic clade except S. jii, and S. yishanensis was the most close to S. ronganensis (Luo et al 2017), it was consistent with the BLAST results (92% identities to the mitogenome of S. ronganensis) and morphological comparison results (Figure 1).…”
supporting
confidence: 85%
“…The gene arrangement and transcriptional orientation in M. electricus are similar to most teleosts (Luo et al. 2017 ; Prakhongcheep et al. 2017 ; Sato et al.…”
mentioning
confidence: 80%
“…The length of two complete circular mitogenomes were 16,570 bp with 44.08% GC content (S. longibarbarus) and 16,582 bp with 43.60% GC content (S. punctatus) respectively. Both genomes consisted of 13 protein-coding genes, 22 transfer RNAs, and 2 ribosomal RNAs, and the arrangement of all genes were identical to other Sinocyclocheilus species known to us (Wu et al 2010;He et al 2016;Luo et al 2017;Peng et al 2017). All genes of two Sinocyclocheilus species were located on the heavy strand (H-strand) except for ND6 gene and eight tRNA genes, and the protein-coding genes started with a traditional ATG except for COX1, which started with one infrequent GTG instead, and terminated with stop codons TAA, TAG, or a single T-base.…”
mentioning
confidence: 86%